Identification and Analysis of Moderator Variables - Sharma, Subhash; Durand, Richard M.; Gur-Arie, Oded (Journal of Marketing Research, 1981)
Although the concept of moderator variables has been used extensively in marketing-related studies, much confusion persists as to how they are defined and identified. To alleviate this confusion, the authors present a typology of moderator variables with a framework for identifying their presence and type. Simulated data are used to illustrate and validate the proposed framework.